To cap/cuff or ring: do distal attachment devices improve the adenoma detection?. (1st February 2019) - Thayalasekaran, Sreedhari; Alkandari, Asma; Varytimiadis, Lazaros; Subramaniam, Sharmila; Coda, Sergio; Longcroft-Wheaton, Gaius; Bhandari, Pradeep
ABSTRACT: Introduction : Colonoscopy reduces the risk of colorectal cancer, by interrupting the adenoma–carcinoma sequence enabling the detection and removal of adenomas before they turn into colorectal cancer. Colonoscopy has its limitations as adenoma miss rates as high as 25% have been reported. The reasons for missed pathology are complicated and multi-factorial. The recent drive to improve adenoma detection rates has led to a plethora of new technologies. Areas covered : An increasing number of advanced endoscopes and distal attachment devices have appeared in the market. Advanced endoscopes aim to improve mucosal visualization by widening the field of view. Distal attachment devices aim to increase adenoma detection behind folds by flattening folds on withdrawal. In this review article, we discuss the three following distal attachment devices: the transparent cap, the Endocuff, and the Endoring. Expert commentary : The authors believe that the distal attachment devices will have a greater benefit for endoscopists with low baseline adenoma detection rates.